HEPATITIS AND HEPATITIS B-ANTIGEN IN GREENLAND - SKINHØJ, PETER; MCNAIR, ALLAN; ANDERSEN, SØREN T. (Oxford University Press, 1974)
The results of this study indicate that viral hepatitis in Greenland occurs as two epidemiologically separate diseases. One type, presumably hepatitis A, occurs in large epidemics with intervals of years between epidemics. The most recent epidemic occurred during 1970–1972. The other type occurs endemically, independent of the epidemics. The endemic hepatitis is characterized by sporadicity, predominance of adult cases, and lack of seasonal fluctuation, indicative of a hepatitis B virus etiology. Hepatitis B-antigen (HB-Ag) was detected in 7.1% of 2904 apparently healthy Greenlanders investigated. The prevalence varied from 1.2 to 12.0% in different areas and was closely related to socioeconomic and housing conditions and inversely correlated with the incidence of endemic hepatitis. No correlation was found to the antigen subtype involved (D or Y). HB-Ag was fivefold more prevalent in children and young adults than in older adults and occurred more frequently in males than in females. The prevalence of healthy HB-Ag carriers is presumably determined by the extent of exposure in early childhood, facilitated by overcrowded housing conditions. In, areas with better living conditions, more individuals remain susceptible to infection in adult life, resulting in clinical hepatitis with transient antigenemia.